Strategies for Implementation of Agricultural Science Curriculum in Imo State School System: Imperatives for Occupational Skills Acquisition by Students - Amadi, Ugochukwu P.N. (Mediterranean Journal of Social Sciences, 2012)
The inability of secondary school graduates of Agriculture to secure jobs or be self-employed has sustainedthe perceived generation gap, which has been blamed on the way and manner in which secondaryeducation Agriculture curriculum is implemented. Four objectives were addressed by the study. A total of200 teachers of Agriculture randomly selected from 298 secondary schools across the three EducationZones of Imo state constituted the study sample. A questionnaire structured on a 4- point rating scale andwith stability coefficients of 0.82, 0.76, 0.70 and 0.86 for sections B to E respectively was used in generatingdata for the study. Findings of the study indicated that some teacher-related factors are necessary foreffective implementation of the curriculum among which is teacher’s moral disposition, commitment, andteaching styles were indicated. Use of modular teaching methods, establishment of good school –community relationships and combined use of performance–based test and written test used for thepurpose of occupation skills acquisition.